IMPLEMENTATION OF THE VALUES OF RELIGIOUS MODERATION IN ARRAUDHAH AMUNTAI ISLAMIC BOARDING SCHOOL - Rukaiyah, Siti; Husin, Husin; Rifa'i, Ahmad (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
Indonesia is a multicultural country, where there are various religions, cultures and ethnicities. Conflicts of contention still occur due to these differences. Instilling the values ​​of religious moderation needs to be applied as a solution to the various differences that exist, both in formal and non-formal institutions. The purpose of this study is to analyze how the values ​​of religious moderation are applied in the Salafiyyah Arraudhah Amuntai Islamic Boarding School. This research uses descriptive qualitative research. The population in this study was the Salafiyyah Arraudhah Amuntai Islamic Boarding School in Pasar Monday village, Amuntai Tengah sub-district, Hulu Sungai Utara district. Data were collected by observation and interviews with the teaching staff at the Islamic boarding school. The results showed that the values ​​of religious moderation were applied by all teachers in various aspects, both in learning and in daily activities. Moderation values ​​applied in Islamic boarding schools include: tolerance, teaching general learning and skills training (obedience to the state), teaching religious learning (obedience to religion) and being open to development and the wider community.